Pengaruh Sinergi, Kredibilitas, Kepemilikan Baru, Budaya, Tata Kelola Perusahaan pada Kinerja Bank Pasca Privatisasi - Limakrisna, Nandan; Juju, Undang (Jurnal Trikonomika, 2008)
In Indonesia, crisis exchange rate was started by the rupiah depreciation and give negative influence to banking sector marked with the increased of the SBI rate till reached 70,8%. This condition caused difficulties of banking industry progressively culminate. At that moment government have taken some policies. One of the policy was found the BPPN. Banks residing under observation of BPPN have come to property of government and next phase government have set mind on to divest. The purpose of this research is to address and learn more about privatization, especially in the banking industry in Indonesia. The focus of this study is to identify the impact of several important variables such as synergy, credibility, new ownership, culture and good corporate governance to the bank performance after privatized. Those five variables are believed to be the critical aspects in the merger and acquisition process. A simple questionnaire has also been developed in order to collect the primary data from target respondents. Respondents in this research are coming from privatized banks, either the bank was privatized through Initial Public Offering or through strategic partner. There were 188 data collected from more than 300 questionnaires distributed. Sequential Equation Modeling has been chosen as the research methodology and Lisrel 8.30 and SPSS 13.0 has also been chosen as the statistic software to be used. These results definitely do not match with the previous research conducted by researchers from other countries, but it could be used to broaden our way of thinking whereby other situation and condition could really produce different result. Banking privatization which have been done not yet had an effect on to improvement of profitability, specially in ROA. Nevertheless, ROA have shown tendency go up. thereby can be concluded that privatisasi yield better performance.